Political information exposure in the 2024 Indonesian election: The case of Indonesian students in India - Mujiburrahman, Mujiburrahman; Joshi, Jaghdish S.; Asbudi, Asbudi; Muslem, Muslem; Mulyadi, Mulyadi; Patty, Alberto Noviano; Hastira, Muh Fichriyadi (SIMULACRA: JURNAL SOSIOLOGI, 2025)
This study explores how exposure to political information through social media influences Indonesian students in India in the 2024 Presidential Election. This study uses a mixed methods approach, combining a quantitative survey of 41 students with in-depth interviews to gain a more comprehensive understanding. Data were collected through online questionnaires and focus group discussions, then analyzed using descriptive statistical techniques and thematic analysis. The results show that Instagram and YouTube are the leading platforms for political information, with 56% of respondents stating that they trust the content they consume. This exposure does not necessarily change political preferences but contributes to increasing political awareness, strengthening digital literacy, and fostering critical thinking. The uniqueness of this study lies in its focus on diaspora students, who are relatively rarely touched upon in the literature on digital politics in Indonesia. Unlike domestic voters who are often influenced by viral issues, Indonesian students in India exhibit more reflective information consumption patterns, influenced by their transnational experiences. These findings confirm that social media functions as a cross-border digital democracy space, highlighting the importance of strengthening digital literacy to ensure more conscious, reflective, and quality political participation among the diasporas.